Correlation Between Age, Work Period, Knowledge, and Attitude’s Workers With Behavior on The Use of PPE - Cynthia Widyawati; Indriati Paskarini (Jurnal Berkala Kesehatan, 2021)
PG. Poerwodadie is one of the white crystal sugar factories left by the Dutch East Indies. In the production process with a fairly high risk of work accidents, the company provides Personal Protective Equipment (PPE). However, most workers have not complied with the use of PPE in the work area. Therefore, it is necessary to research factors related to non-compliance with the use of PPE. The purpose of the study was to determine the relationship between age, years of service, education, and attitudes with workers who were not obedient in using PPE. This research uses quantitative with the cross-sectional approach. The population in this study were all workers at the PG. Poerwodadie manufacturing station totals 80 people. The study concludes that there was a relationship between the age of workers and non-compliance with the use of PPE with the value of Phi and Cramer's V = 0.337. There was a relationship between the working period and non-compliance with the use of PPE with a value of 0.329. There was a relationship between worker knowledge and non-compliance with the use of PPE with the value = 0.279. There was no relationship between worker attitudes and non-compliance with the use of PPE